Gaston - DiPucchio, Kelly; Robinson, Christian (New York : Atheneum Books for Young Readers, 2014)
A proper bulldog raised in a poodle family and a tough poodle raised in a bulldog family meet one day in the park.
Ages 4-8.
Keywords: Poodles -- Fiction; Bulldog -- Fiction; Dogs -- Fiction; Individuality -- Fiction; Poodles -- Juvenile fiction; Bulldog -- Juvenile fiction; Dogs -- Juvenile fiction; Individuality -- Juvenile fiction; Bulldog; Dogs; Individuality; Poodles; Fiction; Juvenile works